An investigation of vegetation effect on the performance of IEEE 802.11n technology at 5.18 GHz. - Torshizi, Seyed Dawood Sajjadi; Lo, Ka Kien; Kwong, Kae Hsiang; Ting, Alvin Kee Ngoh; Heng, David Tze Chieng; Abbas, Mazlan; Lim , Heng Siong; Hashim, Fazirulhisyam (2012)
In this paper, the performance of IEEE 802.11n Wi-Fi technology at 5.18 GHz frequency in one of the rural areas in Malaysia, which is typically covered by dense tropical foliage, is evaluated and analyzed. To our best knowledge, studies on the performance of the IEEE 802.11n technology in foliage area have not been fully explored. We have conducted line-of-sight and non-line-of-sight measurements through the tropical foliage using directional high gain antennas to determine the throughput and other well-known performance metrics. It is observed that by utilizing the key features of 802.11n such as channel bonding and short guard interval, superior performance results can be achieved for both aforementioned situations. Precise correlation of utilized hardware specification and acquired results in different points is another aspect of this work. The findings are useful for future rural wireless deployment particularly with low height antenna using IEEE 802.11n technology.